Laughing gas abuse causing subacute combined spinal cord degeneration with psychiatric manifestations - Maria Ruxandra Docan; Mihaela Aftinia Marian; Anca Adriana Arbune; Elena Marin; Adriana Octaviana Dulamea (Romanian Journal of Neurology)
Background. Nitrous oxide, a nonirritating gas commonly used as an anesthetic, is increasingly abused by the young population for its euphoric effects due to its seemingly harmless nature. However, its neurological impacts can vary in intensity and sometimes result in permanent damage. Accurate diagnosis and treatment hinge on identifying nitrous oxide use through anamnesis, clinical and paraclinical findings, as demonstrated in the following case report. Case report. A 27-year-old female with psychiatric history presented with progressive paresthesia and walking difficulty, admitting to recent nitrous oxide use, alongside other substances. Clinical examination revealed mild tetraparesis, coordination disturbances, generalized hyporeflexia, and sensory deficits. Electromyography showed severe sensory neuropathy, and spinal MRI indicated subacute combined degeneration (SCD) of the spinal cord. Laboratory tests revealed hyperhomocysteinemia and elevated methylmalonic acid levels, despite normal vitamin B12 levels. Treatment included intramuscular vitamin B12, folic acid, and neurotrophic agents, along with physical rehabilitation. Psychiatric symptoms, possibly exacerbated by nitrous oxide, and complicated adherence to therapy. Conclusions. This case underscores the neurotoxic potential of nitrous oxide, particularly its disruption of cobalamin metabolism, and highlights the need for thorough patient histories to uncover substance use contributing to neurological symptoms. Despite treatment, some neurological deficits may persist, emphasizing the importance of early intervention and comprehensive care strategies.